2000
DOI: 10.1074/jbc.m005220200
|View full text |Cite
|
Sign up to set email alerts
|

EGR1 Target Genes in Prostate Carcinoma Cells Identified by Microarray Analysis

Abstract: The EGR1 transactivator is overexpressed in prostate cancer, and its expression pattern suggests that EGR1 could potentially regulate a number of steps involved in initiation and progression of prostate cancer, such as mitogenesis, invasiveness, angiogenesis, and metastasis. To identify potential EGR1 target genes in an unbiased manner, we have utilized adenovirus-mediated expression of EGR1 in a prostate cancer cell line to identify specific genes that are induced by EGR1. Using oligonucleotide arrays, a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 57 publications
(55 reference statements)
7
135
0
1
Order By: Relevance
“…This observation was initially reported by Svaren and colleagues (16) and subsequently confirmed by others (11,17). The importance of this finding is related to the rapid and strong EGR1 increase induced by growth factors, mitogens, cytokines, environmental and mechanical stresses, and DNA damage.…”
Section: Structure and Regulation Of The Cdkn1c Genesupporting
confidence: 63%
“…This observation was initially reported by Svaren and colleagues (16) and subsequently confirmed by others (11,17). The importance of this finding is related to the rapid and strong EGR1 increase induced by growth factors, mitogens, cytokines, environmental and mechanical stresses, and DNA damage.…”
Section: Structure and Regulation Of The Cdkn1c Genesupporting
confidence: 63%
“…Further evidence for a role of Egr1 in oncogenesis was provided by experiments using specific high-affinity Egr1 antisense oligonucleotides. [59][60][61] It was shown that in a series of mouse and human prostate cancer cells, Egr1 antisense inhibited cell proliferation, colony formation, and growth in soft agar, 63 Interestingly, several genes identified in this screen are associated with neuroendocrine differentiation, which is known to occur frequently in murine prostate cancer. Another Affymetrix microarray analysis compared mouse prostate cancer cells TRAMP-C2 in the presence or absence of Egr1 antisense.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
“…[73][74][75] An important feature of the suppressor network in prostate tumors is Egr1-induced TGFb1. 61,63,64 TGFb1 has diverse roles and may have the net effect of promoting the progression of prostate cancer (reviewed in Albrecht et al 72 and Zheng et al 73 ). TGFb1 may also facilitate detachment and metastasis.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
“…The EBS-GFP reporter plasmid was constructed by subcloning the promoter sequence into the AseI-NheI cloning sites. Adenoviral construct expressing EGR-1 was a gift from Dr Jeffrey Milbrandt (Svaren et al, 2000).…”
Section: Plasmid Constructsmentioning
confidence: 99%